Updated and expanded - LaHaye, Tim; (1926-2016) (U.S.A, 1976)
The art of mutually enjoyable lovemaking is not difficult to learn, but neither is it automatic. No one is a good lover by nature, yet no one need settle for a lifetime of sexual frustration. Tim and Beverly LaHaye offer principles, goals, guidelines, charts, and research results to help couples achieve the satisfying relationship every person anticipates when he says, `I do.`
Keywords: Sex -- Religious aspects -- Christianity